De Novo Interstitial Deletion of 9q in a Pediatric Patient With Global Developmental Delay. (7th May 2019) - Keselman, Dennis; Singh, Ram; Cohen, Ninette; Fefer, Zipora
Cytogenomic microarray (CMA) methodologies, including array comparative genomic hybridization (aCGH) and single-nucleotide polymorphism-detecting arrays (SNP-array), are recommended as the first-tier test for the evaluation of imbalances associated with intellectual disability, autism, and multiple congenital anomalies. The authors report on a child with global developmental delay (GDD) and a de novo interstitial 7.0 Mb deletion of 9q21.33q22.31 detected by aCGH. The patient that the authors report here is noteworthy in that she presented with GDD and her interstitial deletion is not inclusive of the 9q22.32 locus that includes the PTCH1 gene, which is implicated in Gorlin syndrome, or basal cell nevus syndrome (BCNS), has not been previously reported among patients with a similar or smaller size of the deletion in this locus suggesting that the genomic contents in the identified deletion on 9q21.33q22.31 is critical for the phenotype.